Internal migration of ethnic groups in Latvia: The importance of age and geography - Krumins, Janis; Berzins, Maris (Quaestiones Geographicae, 2026)
Internal migration plays a key role in population change and distribution. Limited geographic mobility among specific groups may indicate disadvantages, given its significance in population trends and employment fluctuations. Analysing the varying mobility rates across different ethnic groups can elucidate the impact of internal migration on demographic shifts, social and cultural life, and economic development. Despite the relatively high proportion of ethnic minorities within Latvia’s population, there is a paucity of research on the differences in internal migration propensities and flows by ethnicity. This research paper examines the ethnic dimension of changes in usual residence using one-year data from the Population Census (2011) and Population Register (2019). The findings reveal significant disparities between the ethnic and age group cohorts of internal migrants and the total population in the rural and urban areas of Latvia, thereby underscoring the importance of the settlement system in the overall transformation of population composition.